2021
DOI: 10.1186/s12913-021-06265-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of advance care planning practices among people with chronic diseases in hospital and community settings: a retrospective medical record audit

Abstract: Background Advance Care Planning (ACP) enables healthcare professionals to embrace the important process where patients think about their values in life and goals for health care, and discuss their future health care preferences with family members for a time when they are not able to make health care decisions. Despite the promotion of ACP last two decades, and well-known benefits of ACP and a written Advance Care Directive (ACD), they are still underutilised in Australia and across the world.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…However, various terms appear with variations in jurisdictional legislation, for example, an EG in Australia and ‘Lasting Power of Attorney for Health and Welfare’ in the UK [ 36 ], and ‘a legal proxy’ in German [ 37 ], even with a consensus that ACP includes ACDs and the appointment of a proxy decision maker [ 38 ]. The challenges with the lack of uniform term across the world include misunderstanding of the responsibility and legality, and underreporting or misreporting of the prevalence of EG [ 35 , 39 ]. This study specified the definition of an EG in Australian context (See Supplementary file 2 ) to increase clarity and accuracy of the results.…”
Section: Discussionmentioning
confidence: 99%
“…However, various terms appear with variations in jurisdictional legislation, for example, an EG in Australia and ‘Lasting Power of Attorney for Health and Welfare’ in the UK [ 36 ], and ‘a legal proxy’ in German [ 37 ], even with a consensus that ACP includes ACDs and the appointment of a proxy decision maker [ 38 ]. The challenges with the lack of uniform term across the world include misunderstanding of the responsibility and legality, and underreporting or misreporting of the prevalence of EG [ 35 , 39 ]. This study specified the definition of an EG in Australian context (See Supplementary file 2 ) to increase clarity and accuracy of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Early planning is particularly important for older adults with frailty as they are likely to develop adverse outcomes and deteriorate unexpectedly (Clegg et al, 2013; Covinsky et al, 2003). Yet, ACP continues to be underutilized in long‐term care settings (De Gendt et al, 2013; Jeong et al, 2021; Knight et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…4 Low rates of ACP engagement are unfortunately not unique to Canada. 5 A recent Australian survey found that only 15% of adults had completed ACP documentation, 6 while studies in Northern Ireland and Singapore found rates of having had an ACP discussion to be 7% and 12.5%, respectively. 7,8 ACP education and conversations have generally been restricted to the health system, but in a recent study, healthcare providers reported insufficient time and their own lack of knowledge as significant barriers.…”
Section: Introductionmentioning
confidence: 99%